2022
DOI: 10.3390/ijerph19031739
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Implementation of Preventive Measures Due to COVID-19 on Work Design and Early Childhood Professionals’ Well-Being—A Qualitative Study

Abstract: The reopening of child-care programs during COVID-19 demanded comprehensive preventive measures. Research to date has overlooked this reopening process as well as early childhood professionals’ (ECPs) implementation efforts and resulting changes in their work practices and well-being. As a result, this study sought insights into (1) the practical implementation of measures, (2) perceptions and evaluations of measures, (3) changes in work characteristics, and (4) its impact on well-being. Qualitative interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 113 publications
2
10
0
5
Order By: Relevance
“…Many workers felt they had essentially taken on entirely new jobs or were doing multiple jobs at once without a corresponding change in pay, preparation, or respect, and with higher exposure to risk. These findings align with and add to a review of other ECE workforce studies and reports from the United States conducted as of early 2021 and several studies published since then [ 13 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 86%
“…Many workers felt they had essentially taken on entirely new jobs or were doing multiple jobs at once without a corresponding change in pay, preparation, or respect, and with higher exposure to risk. These findings align with and add to a review of other ECE workforce studies and reports from the United States conducted as of early 2021 and several studies published since then [ 13 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 86%
“…In der vorliegenden Studie zeigten Beschäftigte mit Leitungsfunktionen einen höheren ERI-Score sowie eine höhere Verausgabungsbereitschaft als Beschäftigte ohne Leitungsfunktion (p < 0,001). Im Rahmen dieser Studie lässt sich die Präsenz einer höheren Verausgabungsbereitschaft möglicherweise auf das verstärkte Verantwortungsgefühl hinsichtlich des Gesundheits-und Arbeitsschutzes von Leitungskräften zurückführen, wie KiTa-Leitungen in einer qualitativen Studie während der COVID-19 Pandemie berichteten [3]. Ein höherer ERI-Score für Leitungskräfte in Kindertagesstätten wurde ebenfalls in einer Vorgängerstudie vor der COVID-19-Pandemie gefunden [13].…”
Section: Diskussionunclassified
“…B. durch überbordende Bürokratie), schwache Wertschätzung durch Politik und Gesellschaft sowie körperliche Belastungen, verstärkt durch schlechte Ergonomie [1,2]. Erste Studien während der COVID-19-Pandemie betonen diese Belastungsfaktoren wie ein erhöhtes Arbeitspensum oder mangelnde gesellschaftliche Anerkennung [3] und identifizieren zusätzliche Belastungsquellen wie fehlende persönliche Schutzausrüstung oder unzureichende Testkapazitäten [4].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…So far, only few studies focused on the pandemic situation in ECEC centres, especially regarding the consequences of the pandemic for the educational work in the centres. There are qualitative and quantitative studies that confirm higher stress levels among the pedagogical staff in the pandemic (Bigras et al, 2021), caused among others by a higher workload due to implementation efforts, low social support (Gritzka et al, 2022;Triandafilidis et al, 2022), fears of COVID-19 or structural problems, like staff shortage (Kuger et al, 2022). The latter study moreover confirmed decreasing well-being by ECEC children and their parents in times of the pandemic (ebd.).…”
Section: Interactions In Ecec Centres As a Key Factor For Children's ...mentioning
confidence: 99%